Artistic expression as a source of resilience for transgender and gender diverse young people. Issue 2 (3rd April 2023) - Austin, Ashley; Dentato, Michael P.; Holzworth, Joshua; Ast, Roxanna; Verdino, Anthony P.; Alessi, Edward J.; Eaton, Andrew D.; Craig, Shelley L.
Abstract: There is a paucity of research exploring sources of resilience among transgender and gender diverse (TGD) young people with multiple marginalized identities. Information and communication technologies (ICTs) offer unique opportunities for authentic self-expression, which is not always possible offline. The primary aims of this study were to understand unique sources of resilience among TGD youth in their online and offline lives. Using photo elicitation and grounded theory methods, we conducted online in-depth interviews with TGD young people ( N = 29) between the ages of 14–25 across the United States identifying with at least one of the following social statuses: (a) person of color, (b) immigrant, or (c) living in a rural area. Four themes were identified from the data, with both online and offline artistic expression being viewed as a: (1) form of authentic self-expression; (2) coping mechanism; (3) way to connect to others; and (4) pathway toward agency. Findings advance understanding about the use of artistic expression as an underexamined source of resilience among TGD youth with multiple marginalized identities. Within clinical settings, options for TGD youth to participate in various forms of expressive art may improve engagement and enhance youths' abilities to authentically express their thoughts, feelings, and experiences to promote healing and growth.